Usefulness of a routine endoscopic assessment of laryngeal lesions after lung cancer surgery. Issue 1 (4th August 2017) - Fourdrain, Alex; De Dominicis, Florence; Iquille, Jules; Lafitte, Sophie; Merlusca, Geoni; Witte Pfister, Alejandro; Bagan, Patrick; Berna, Pascal
ABSTRACT: Background and objective: Laryngeal pathology following lung cancer surgery is associated with post‐operative morbidity and mortality. The aim of our study was to evaluate the usefulness of routine endoscopic assessment. Methods: We prospectively evaluated vocal cord pathology using laryngeal endoscopy within 24 h post‐surgery. Over 25 months, 276 patients underwent thoracic surgery. We excluded 26 patients with previous laryngectomy or vocal cord paralysis, early post‐operative reintubation or patients who did not consent to an endoscopy. Endoscopic data were reported using a standardized procedure, recording vocal cord paralysis, swallowing disorders with aspiration, detected using a blue‐coloured water test and vocal cord haematoma. Results: Among 250 patients, vocal cord paralysis was diagnosed in 13 patients (5.2%) and was associated with a higher rate of post‐operative pneumonia ( P = 0.03), post‐operative bronchoscopy ( P = 0.01), reintubation ( P = 0.007) and a trend towards an increased 90‐day mortality rate ( P = 0.09). Swallowing disorders with aspiration were diagnosed in 18 patients (7.2%) and were associated with a higher rate of post‐operative pneumonia ( P = 0.007), post‐operative bronchoscopy ( P = 0.01), reintubation ( P = 0.004) and 90‐day mortality ( P = 0.03). Vocal cord haematomas were diagnosed in 28 patients (11.2%) and were not associated with an increased post‐operative morbidity or mortality. Conclusion: Post‐operative endoscopic laryngeal assessment is effective for diagnosing laryngeal pathology following thoracic surgery. Routine laryngeal endoscopic assessment may detect clinically silent swallowing disorders early to allow prompt treatment, which may prevent respiratory complications. Abstract : See related Editorial Post‐operative endoscopic laryngeal assessment is effective in diagnosing laryngeal lesions following pulmonary resection. These lesions are associated with respiratory morbidity, especially aspiration, and mortality. Routine post‐operative laryngeal endoscopic assessment may help diagnose these lesions early and enable prompt treatment.